The Investment Decision of the Post-Keynesian Firm: A Suggested Microfoundation for Minsky's Investment Instability Thesis - James Crotty; Jonathan Goldstein (Levy Economics Institute of Bard College, 1992)
In this paper, Crotty and Goldstein undertake the formulation of a model of enterprise investment decision that can provide a microeconomic foundation for the Keynes-Minsky macromodels developed by Delli Gatti & Gallegati, Jarsulic, Semmler and others. The authors address the difficulties inherent in the formulation of an investmes theory in which the future is unknowable, and investment substantially irreversible. Where Minsky accepts a variation of the Tobin-q theory-in which owners and managers are assumed to be identical economic agents-Crotty and Goldstein look to Keynes' insistence on their qualitative difference. Financial commitments to creditors are certain, while expected profits are not. Thus, the interests of stockholders and other creditors represent a potential threat to the autonomy management needs to ensure the security of the enterprise itself. The authors derive the comparative static properties of the optimal investment decision, the essence of which they show to be the growth-safery tradeoff whereby management must sacrifice financial security to obtain growth and vice-versa. The model is shown to be able to generate both the "waiting to invest" result of the irreversible investment literature, and the major theoretical relation empirically tested and confirmed by Fazzari, Hubbard and Peterson (1988). This model explains a demand side effect rather than a supply side influence. The many subjective and financial variables in the model reflect: i)managerial attitudes, ii) management's confidence in its ability to forecast meaningfully, iii) the financial status of the firm, and iv) the profit markup. This theory is too complex to find incorporation in a formal, mathematical business cycle model. However, using the example of the end-of-expansion, onset-of-crisis phase of a Minsky cycle, the authors show that their results can be used to model the characteristics of post-war business cycles in a manner consistent with Minsky's work.
Keywords: 330